HLA-A*68:02-restricted Gag-specific cytotoxic T lymphocyte responses can drive selection pressure on HIV but are subdominant and ineffective. - Kløverpris, H; Stryhn, A; Harndahl, M; Carlson, J; Leslie, A; Chen, F; Riddell, L; Mulenga, J; Walker, B; Ndung'u, T; Buus, S; Goulder, P (2013)
BACKGROUND: Human leukocyte allele (HLA) class I polymorphism has the greatest impact of human genetic variation on viral load set point. A substantial part of this effect is due to the action of HLA-B and HLA-C alleles. With few exceptions the role of HLA-A molecules in immune control of HIV is unclear. METHODS: We here study HLA-A*68:02, one of the most highly prevalent HLA-A alleles in C-clade infected sub-Saharan African populations, and one that plays a prominent role in the HIV-specific CD8 T-cell responses made against the virus. RESULTS: We define eight epitopes restricted by this allele and propose the peptide binding motif for HLA-A*68:02. Although one of these epitopes almost exactly overlaps an HLA-B*57-restricted epitope in Gag linked with immune control of HIV, this HLA-A*68:02-restricted Gag-TA10 response imposed only weak selection pressure on the virus and was not associated with significantly lower viral setpoint. The only HLA-A*68:02-restricted responses imposing strong selection pressure on HIV were in the flanking regions of Pol-EA8 and Pol-EA11 and within the Vpr-EV10 epitope (P  =  8 × 10). However, targeting of this latter epitope was associated with significantly higher viral loads (P  =  0.003), suggesting lack of efficacy. CONCLUSION: This study is consistent with previous data showing that HLA-A-restricted Gag-specific responses can impose selection pressure on HIV. In the case of HLA-A*68:02 the Gag response is subdominant, and apparently has little impact in natural infection. However, these data suggest the potential for high frequency vaccine-induced Gag responses restricted by this allele to have significant antiviral efficacy in vaccine recipients.